Mind and Body in Sync: The Fascinating Field of Psychophysiology in Sports - Navabinejad, Shokouh; Rostami , Mehdi (Health Nexus, 2023)
This letter to the chief editor delves into the captivating world of psychophysiology in sports, an interdisciplinary field that explores the dynamic interplay between the mind and body in athletic contexts. It outlines the fundamental concepts of psychophysiology, emphasizing its significance in understanding how psychological states influence physical performance. The letter highlights key historical developments and pivotal research that have shaped our understanding of this field, illustrating how psychophysiological principles have been integrated into sports science. It further discusses the practical applications of these principles in enhancing sports performance, including techniques like biofeedback, mental training, and stress management. The letter addresses existing challenges in the field, such as the need for comprehensive research and the integration of psychophysiological practices in training regimens. It concludes with a forward-looking perspective, emphasizing the potential for future advancements and the importance of continued exploration in this area. The letter aims to draw attention to the importance of psychophysiology in sports, advocating for greater recognition and application within the sports community, and suggesting a pathway for future research and collaboration.